Fiscal policy in Mediterranean countries – developments, structures and implications for monetary policy - Michael Sturm; François Gurtner (European Central Bank (ECB), 2007)
Southern and eastern Mediterranean countries have many fiscal challenges in common with other emerging market and mature economies concerning deficit and debt reduction and the maintenance of fiscal discipline. However, most countries in the region also face some specific fiscal issues, such as relatively high public debt, dependence on some form or another of donor dependence or concessional financing, high budgetary exposure to fluctuations in hydrocarbon prices, high defence expenditure and weak tax bases. Against this background, this paper reviews fiscal developments and fiscal policy issues in the ten countries that are participants or observers in the EU's Barcelona process. The main focus is on the implications of these developments and issues for macroeconomic stability, given that countries in the region have made considerable progress in terms of macroeconomic stabilisation over the last two decades, which is reflected in particular in lower inflation rates. The analysis distinguishes between non-oil-producing and oil-producing countries in the region, as they exhibit different fiscal features and are confronted with different challenges. In the case of non-oil-producing countries, the key challenges stem from high deficits and debt levels, including implicit and contingent liabilities, notwithstanding some progress in fiscal consolidation in most of these countries over the last years. In the case of oil-producing countries, whose fiscal situation has significantly improved in recent years in the wake of high oil prices, the key challenges for fiscal management stem from the heavy reliance on an exhaustible source of revenues and a large exposure to fluctuations in international hydrocarbon prices. A shock originating from – or being transmitted via and exacerbated by – the fiscal sector appears to be the single most important macroeconomic risk in many countries.
Keywords: 330; Finanzpolitik; Mittelmeerraum